DEVELOPMENT OF JAYAWIJAYA LOCAL WISDOM TEACHING MATERIALS TO IMPROVE SCIENCE PROCESS SKILLS - Jan Pieter; Triwiyono Triwiyono; Putu Victoria M. Risamasu (Jurnal Ilmu Pendidikan Indonesia, 2023)
The absence of teaching materials with a local context is an obstacle to the implementation of science learning in areas where the mother tongue is still dominant in daily communication. Related to this reality, this study aims to develop and validate teaching materials in the context of Jayawijaya local wisdom that can be used to improve students' science process skills. The method used is the research and development (R&D) method by adopting the 4D (Four D) model developed by Thiagarajan and Melvyn (1974). The results of data analysis carried out by 5 validators stated that the teaching materials developed were very feasible for use in science learning. The content expert and media expert validators gave an average score of 93.83 (very good) and the practitioner validator assessed 97.12 (very good). The results of the validation show that the teaching materials in the context of local wisdom that are developed are feasible and can be used in science learners at school